Variable influence of ferric and cupric ions on Saccharomyces cerevisiae strains used in asymmetric organic synthesis. - Pereira, R. D.; Duran, N. (Chapman Hall Ltd, 1996)
Fe (III) and Cu (II) each at 50 mu M in four commercial strains of Saccharomyces cerevisiae induced an increase of NAD(P)(+) reduction in one strain (Turkish), but two others (Chilean and Brazilian), the presence of Fe(III) and/or Cu(II) diminished NAD(P)(+) reduction presumably due to free radicals formation inside these living cells. Suprisingly, in the American strain, Fe(III) induced a decrease and Cu (II) an increase of NAD(P)(+) reduction.